Toxic Heritage Legacies, Futures, and Environmental Injustice - Kryder-Reid, Elizabeth; May, Sarah (Key Issues in Cultural Heritage, 2024)
Toxic Heritage addresses the heritage value of contamination and toxic sites and provides the first in-depth examination of toxic heritage as a global issue. Bringing together case studies, visual essays, and substantive chapters written by leading scholars from around the world, the volume provides a critical framing of the globally expanding field of toxic heritage. Authors from a variety of disciplinary perspectives and methodologies examine toxic heritage as both a material phenomenon and a concept. Organized into five thematic sections, the book explores the meaning and significance of toxic heritage, politics, narratives, affected communities, and activist approaches and interventions. It identifies critical issues and highlights areas of emerging research on the intersections of environmental harm with formal and informal memory practices, while also highlighting the resilience, advocacy, and creativity of communities, scholars, and heritage professionals in responding to the current environmental crises. Toxic Heritage is useful and relevant to scholars and students working across a range of disciplines, including heritage studies, environmental science, archaeology, anthropology, and geography.